Pengaruh Model Quick on the Draw Berbasis Media Troley Belanja terhadap Kemampuan Numerasi Matematika Siswa Kelas V Sekolah Dasar - Priska Lusiana Septiani; Intan Susetyo Kusumo Wardhani; Wahyu Nugroho (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Elementary school students' mathematical numeracy skills remain a significant concern, as indicated by difficulties in understanding numerical information, developing problem-solving strategies, and applying mathematical concepts in everyday life. Teacher-centered learning has limited students' active participation, highlighting the need for a more engaging and contextual learning model. This study aimed to determine the effect and effectiveness of the Quick on the Draw learning model based on shopping trolley media on the mathematical numeracy skills of fifth-grade elementary school students. The study employed a quantitative approach using a quasi-experimental method with a non-equivalent control group design. The sample consisted of 59 students, including 28 students in the control class and 31 students in the experimental class, selected through purposive sampling. Data were collected through observation, interviews, and pretest and posttest assessments, and were analyzed using normality and homogeneity tests, an independent samples t-test, and N-Gain analysis. The results showed a significance value of 0.000 (< 0.05), indicating a significant difference in numeracy skills between the two groups. The mean score of the experimental class increased from 45.1 to 88.1, with an N-Gain score of 80.23%, which was categorized as effective. In contrast, the control class obtained an N-Gain score of 18.86%, which was categorized as ineffective. Therefore, the Quick on the Draw learning model based on shopping trolley media was proven to have a significant and effective impact on improving the mathematical numeracy skills of fifth-grade elementary school students.